(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim- The purpose of this study was to evaluate the amount of microleakage in the copings fabricated by three different techniques. Materials and Methods- Total of 60 premolar teeth specimens were collected. Individual teeth preparation was done. Impressions were recorded and dies were prepared. They were divided into different groups based on their technique of fabrication of prosthesis. In Group-A, thirty copings were fabricated using direct metal laser sintering (DMLS). In Group –B, other thirty copings were fabricated using milling technique (CAD-CAM). In Group C, the remaining thirty specimens received copings fabricated using conventional casting techniques. Type-1 of Glass ionomer cement was used to lute the prosthesis to the underlying tooth structure. The luted specimens were subjected to thermocycling, in order to simulate thermal stresses and ageing of the cemented crowns. They were immersed in bath of 2% methylene blue solution for 48 hours. Later the specimens were sectioned at the middle, microleakage was observed under stereomicroscope (SZM-45N Zoom Stereo Microscope) at 40X magnification. Statistical Exam nation- The data from all the groups were evaluated using Chi square test using SPSS software (SPSS 12.0;SPSS, INC,Chicago III). Results- in Group A, 70% of the samples has a score of 0 and 30% has a score of 1. In Group B, 30% of the samples has a score of 0, 50% has a score of 1 and 20% has a score of 2. In Group C, 5% of the samples has a score of 0, 20% has a score of 1, 30% has a score of 2, 20% has a score of 3 and 25% has a score of 4. Conclusion- The copings fabricated using direct metal laser sintering (DMLS, Group A) had shown improved marginal fit and reduced microleakage.